Liver Transplantation in the Context of Acute-On-Chronic Liver Failure (ACLF): Where Do We Stand in 2025? - Sébastien L’Hermite; Sébastien L’Hermite; Valentin Coirier; Florent Artru; Florent Artru (Transplant International)
Acute-on-chronic liver failure (ACLF) is a critical condition that arises in the context of advanced liver disease, marked by rapid liver function deterioration and associated multi-organ failure. This syndrome is associated with a major short-term mortality risk, requiring aggressive and specialized clinical care. Despite ongoing efforts, effective therapeutic options for ACLF are lacking, with liver transplantation (LT) considered the only life-saving intervention, yielding acceptable outcomes in carefully selected patients. However, the place of LT for ACLF remains a matter of debate, given the high prevalence of the syndrome, the sickness of liver transplant candidates, the persistent shortage of available liver grafts, and the increasing number of indications to LT. This review aims to provide a comprehensive analysis of the role of LT in ACLF, evaluating current evidence on patient selection, optimal timing for transplantation, and ongoing debates surrounding this practice, specifically the rationale for prioritizing graft allocation for this indication. Furthermore, we will explore global management strategies for ACLF, focusing on bridging patients to LT and improving survival outcomes. Through this review, we seek to enhance understanding of the evolving role of LT in ACLF and offer insights into future directions for clinical practice and research in this critical area.